ZONA PENYANGGA HIJAU STUDI KASUS PADA TEMPAT PEMROSESAN AKHIR SAMPAH DI MANGGAR KOTA BALIKPAPAN - Mulya, Widya; Sari, Iin Pratama; Purwanti, Sri; Simanungkalit, Rifka Mahdalena (IDENTIFIKASI, 2022)
Final Processing Site (TPA) is a place that processes and returns waste to environmental media. Throughout 2021, the average daily waste volume will reach 390.65 tonnes. There are seven landfill zones in Manggar, zones 1 to 4 have been planted with vegetation and are being used as buffer zones, zone 5 has just been closed, zone 6 is currently receiving waste, and zone 7 is a waiting zone. Reforestation of TPA land is needed for several purposes including improving environmental aesthetics, as a buffer zone to prevent excessive odors and flies. The research objective was to determine the condition of the case study green buffer zone at the final waste processing site in Manggar City of Balikpapan. This research was conducted by observing the green buffer zone in the form of green belt thickness and plant species, interviewing employees and the local community about odor and noise disturbances from Final Processing Site (TPA) activities. Based on the results of observations of the buffer zone, from 34 observation points there are 23 observation points with a green belt thickness of less than 100 meters, but if it refers to the regulations regarding Green Open Space (RTH), the TPA area is 49.89 ha with an open area of ​​7.7 ha. then TPA still has green open space of 42.19 ha (according to the minimum green open space regulations of 30% of the landfill area which is 14.967 ha). Based on the results of interviews and observations of secondary air quality data (chemical parameters that give rise to an unpleasant odor) and noise analyzed in the TPA area and in the local residential area, it shows that there have been no complaints from the local community about the smell and noise from TPA activities, the results of secondary data analysis air quality and noise also show values ​​that are still below the quality standards.